Avaliação do desempenho da modelagem hidráulica unidimensional e bidimensional na simulação de eventos de inundação em Colatina/ES - Marlon Marques Coutinho (2015)
The HEC-RAS 1D and HEC-RAS 2D 5.0 flood hydraulics models are tested in Colatina-ES. Models simulations of hydrometric data are compared with observed hydrometric data. Model predictions of inundation extent are compared with inundated area using the measure of fit F proposed by Horritt & Bates (2002). The hydrographs and flood extent used in this analysis are related to floods of 19 and 24 December 2013. Before evaluating the hydraulic models, a sensitivity analysis of the measure of fit F was performed to verify whether the inclusion of the surface area of the riverbed in the comparison of the simulated and observed flood extent induces better results. Another aspect evaluated was whether a parameter set calibrated against data from an event with a certain magnitude will be valid for a more extreme event. Also been verified the effects of the use of larger sized cells in 2D model on the computational processing time, the accuracy of representation of hydrograms and inundation observeds. It was found that the measure of fit F is sensitive to the use of the river channel, in other words, can mask the results indicating good superposition of the observed and simulated inundation areas. In the case of the 2D model, there was no loss of accuracy of hydrometric data in the main channel of the river in the simulations with larger cells. The results confirm that the HEC-RAS models, 1D and 1D / 2D, in Colatina, may be calibrated with most frequent hydrometric data and used to simulate a more extreme event. Thus, are performed the simulation of Feb/1979 great flood. No significant differences were found in the results of the performance of HEC-RAS 1D and HEC-RAS 2D 5.0 models in their ability to predict inundation extent in Colatina. The advantage of HEC-RAS 1D model over 1D / 2D is the simplicity of construction of the topological model, which facilitates the convergence of simulation. The main advantage of HEC-RAS 5.0 2D was to obtain information of the variables (velocity and depth) in the regions of interest.